MINAT TERHADAP PRESTASI BELAJAR MAHASISWA STKIP PARIS BARANTAI KOTABARU - Agus Syarifuddin (STKIP Paris Barantai, 2011)
One of education problems is enthusiasm to teacher profession (teachership enthusiasm) and the relation of with achievement of student learning. Realized that enthusiasm is psychology factor which can create certain condition at someone learning process causing can influence success or fails it in reaching purpose. At education psychology is told, there is four factors relating to enthusiasm, that is motif, motivation, desire, and will;desire. From fourth of faktorini some educationists equalizes the understanding.Known that possibility that the many variables which can influence success of protege, however teacher as educator is directly gives Iesson matter in class as according to curriculum which has been specified and gives evaluation. That way the things of teacher which propesional always claimed to increase its the ability.Â Keywords: Minat, Belajar Mahasiswa, Prestasi